Pelatihan Dan Pendampingan Perhitungan Harga Pokok Produksi Dalam Menentukan Harga Jual Pada Usaha Frozen Food Yasaka 57 Di Sidorejo Kidul, Kec. Tingkir, Kota Salatiga - Erna Sudarmawanti; Fudji Sri Mar’ati; Mada Adi Wibowo (Jurnal Pengabdian Masyarakat (JUDIMAS), 2026)
This community service program partners with SMEs, namely the Yasaka 57 Frozen Food Business, located in Sidorejo Kidul Village, Tingkir District, Salatiga City. The frozen food business uses cassava as the basic ingredient with various processed products. SMEs play a very large role in advancing the Indonesian economy so that SMEs become an alternative provider of employment with various innovations produced and can reduce existing unemployment. The problem found is to classify fixed and variable costs and does not know what costs are included in overhead costs. The solution has been done is to provide literacy about the cost of production at the Yasaka 57 SMEs, Providing training and assistance in the utilization of production cost calculation, Providing training and assistance in production cost calculation and Providing training and assistance in production cost reporting. The implementation method is by means of intensive assistance and guidance with the stages (Planning, Implementation and Evaluation) the last is the result of the service, SMEs has been able to calculate the cost of production by means of inaccurate calculations into more accurate calculations according to cost accounting science and the Owner of Yasaka 57 Frozen Food SMEs in compiling production cost reports more accurately.